2019
DOI: 10.21203/rs.2.14859/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying risk factors of anemia among women of reproductive age in Rwanda - a cross-sectional study using secondary data from the Rwanda Demographic and Health Survey 2014/2015

Abstract: Background Anemia among Women of Reproductive Age (WRA) continues to be among the major public health problems in many developing countries, including Rwanda, where it increased in prevalence between the 2015 and 2010 Rwanda Demographic and Health Survey (RDHS) reports. A thorough understanding of its risk factors is necessary to design better interventions. However, to the best of our knowledge, no study has been conducted in Rwanda on a nationally representative sample to assess factors associated with anemi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…This finding is consistent with the findings from other studies in low and middle-income countries, which found that the associated factors of anemia among women living in the lowest wealth status were increased when compared with those living in the heights wealth status (11,18,20,22,23,33).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with the findings from other studies in low and middle-income countries, which found that the associated factors of anemia among women living in the lowest wealth status were increased when compared with those living in the heights wealth status (11,18,20,22,23,33).…”
Section: Discussionsupporting
confidence: 92%
“…Multiple deficiencies tend to cluster within individuals, and the synergistic effect of these deficiencies is important in the development of anemia in rural residency (39,42,45,46). Other than residency and socioeconomic status, women who were not used hormonal contraceptive, younger age category, and no education and married were potential predictors of anemia among the studied participants in Ethiopia; other studies have reported a similar relation (4,9,10,18,23,24,33,46).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A study in Dhaka showed a strong relationship between maternal age, education level, income level, and maternal Hb concentration [18]. Moreover, higher BMI, primiparity, and living in better-off households were associated with higher levels of Hb [21, 22]. On the contrary, low family income and large family size are negatively associated with maternal Hb concentration [24].…”
Section: Introductionmentioning
confidence: 99%